Pengaruh Worklife Balance Dan Self Efficacy Kerja Terhadap Kinerja Pegawai Pada Kantor Balai Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Kelautan, Teknologi Informasi Dan Komunikasi (BPPMPV-KPTK) Gowa - Ramadaniel, Baso Reski; Latif, Nurdin; Saharuddin, Andi (STIM-LPI Makassar, 2024)
This study aims to determine the worklife balance and self efficacy on employee performance at the Office of the Center for the Development of Quality Assurance of Vocational Education in the Marine, Fisheries, Information and Communication Technology (BPPMPV-KPTK) Gowa. The method used in this study is a quantitative method with a total of 56 employees respondents who are used as samples with sampling techniques, namely probability or random samples with sloving techniques, where data collection techniques use questionnaires. The analysis used in this study was a multiple linear regression test. The results of simulated testing of worklife balance and self-efficacy variables have a positive and significant effect on employee performance variables as evidenced by simultaneous test results with a significance value of f<α (0.000<0.05). The results of partial testing of worklife balance variables have a positive and significant effect on employee performance variables with a significance value of f<α (0.000<0.05). The results of partial testing of self-efficacy variables have a positive and significant influence on employee performance with a significance value of f<α (0.000<0.05).